Effective Strategy: The Influence of Brand Image and Service on Expedition Service Purchase Decisions - Aliisa Zanuba Aripah Chavsoh; Irena Larashati; Imelda Megawati; Haris Nurdiansyah (Majalah Bisnis & IPTEK, 2025)
This research is driven by issues faced by an expedition company in Bandung. The company is characterized by subpar service and brand image, which are attributed to various factors stemming from human error that impact purchasing decisions. This study seeks to ascertain the impact of brand image and service quality on service purchasing decisions.  The employed study methodology is quantitative, utilizing a descriptive and verification technique. The sample includes 100 respondents who are consumers of excursion services. Primary data, namely data collected directly from consumers of an excursion company in Bandung, is utilized to get supporting information. The employed data analysis method is multiple linear regression.  The findings of this study demonstrate that partial Service Quality exerts a positive and substantial influence on the independent variable (X1), with a p-value of 0.000, which is below the significance threshold of 0.05. Brand Image and Service Quality positively and substantially influence Service Purchase Decisions, with a significance value of 0.000, below the 0.05 threshold.